Transcriptome response in a marine copepod under multigenerational exposure to ocean warming and Ni at an environmentally realistic concentration - Yunlei Zhang; Shiru Lin; Yaolu Niu; Xiaoping Zhou; Qingxian Lin (Ecotoxicology and Environmental Safety)
Due to anthropogenic activities, coastal areas have been challenged with multi-stresses such as ocean warming and nickel (Ni) pollution. Currently, studies have concerned the combined effects of Ni and warming in marine organisms at the phenotypic level; however, the underlying molecular mechanisms are poorly known. In this study, a marine copepod Tigriopus japonicus was maintained under warming (+ 4℃) and an environmentally realistic level of Ni (20 μg/L) alone or combined for three generations (F0-F2). Transcriptome analysis was performed for the F2 individuals. We found that the gene transcripts of copepods were predominantly down-regulated after Ni and warming exposure. Based on the results of GO and KEGG analysis, chitin metabolism, detoxification, antioxidant, apoptosis, and energy metabolism were screened in this study. Among the above functions, the combined exposure enriched more differential expression genes and had a larger fold change compared to Ni exposure alone, suggesting that warming increased the negative effect of Ni on marine copepods from a molecular perspective. Specifically, the combined exposure exacerbated the down-regulation of defense, apoptosis, xenobiotic efflux, GSH system, and energy metabolism, as well as the up-regulation of detoxification and peroxidase system. Overall, this study indicates that both ocean warming and Ni pollution adversely affect the marine copepod T. japonicus from multigenerational transcriptome analysis, especially warming increased Ni toxicity to marine copepods, and our results also provide references to the mechanism concerning the effects of Ni and warming on marine copepods.